Transforming a Failed Business Concept into Success by Entering a Foreign Market – A Case Study of a Finnish Service Industry MNE - Uotinen, Sakari (My University, 2019)
While previous studies have thoroughly addressed the foreign market entry modes, they lack an inclusion of risk assessment methods in determining whether an MNE or SME should enter a foreign market. Therefore, this exploratory study examines the role of a single service industry MNE in the field of internationalization by determining the process of internationalization and entry mode choice by using both quantitative as well as qualitative methods. This study also differs from previous research by focusing on a foreign market that has already been successfully penetrated by the MNE, and in addition, on a concept that has failed to generate profit in the home country market. This thesis presents a unique situation in which parent company MNE seeks to launch its prototype- like subsidiary to develop its offering after the subsidiary and its service failed to generate profit in the home country. The focus of the study is on addressing the factors that caused the previous failure, offering insights on the factors that motivate service industry MNEs with unique concepts to internationalize, while presenting further information on how the case company chooses to enter markets and which factors affect the entry mode decision. In order to gain a broad understanding of the factors that may have the potential to pose a threat after the proposed foreign market has been penetrated by the new subsidiary, this study utilizes not only the top management, but former employees as well. In addition to subjective and qualitative data, this thesis employs the use of financial statements to add quantitative and objective data into the analysis. The findings of this study indicate the underlying problems that caused the previous failure in both qualitative and quantitative manner, assess the characteristics of the proposed new foreign market, showcase the entry mode motivators, and indicates whether a company should seek to enter a foreign market with its new subsidiary in the first place by using risk assessments tools. Therefore, this thesis offers a unique insight not only to assess the entry modes, but to also investigate and correct the underlying problems that may pose a threat for the success of the new entry.
Keywords: foreign market entry; single case study; risk management; non-manufacturing firm; SME; MNE; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|